Local and divergent patterns of technological learning within (partly) globalized markets: Is there anything new? And what can policies do about it? A concise guide - Giovanni Dosi; Carolina Castaldi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
In this work, we present an assessment of the nature and impact of current globalizing tendencies at various levels of observation. The evidence in this respect suggests that it has mostly concerned financial flows (especially short-term ones); to some extent trade flows; and only to very limited degrees, if any, the modes of access to new (and even old) technologies. A widely held prejudice is that globalization goes hand in hand with international convergence in technological capabilities and incomes: in quite a few cases the opposite indeed holds. Conversely, such evidence powerfully hints at the continuing role of public policies in fostering the accumulation of technological knowledge and its economic exploitation. We suggest some taxonomies of the control and state variables which policies are likely to influence. Beyond the fading away wave of market fundamentalism - we suggest - it is high time to pragmatically re-assess the role of markets as often powerful, but highly imperfect, mechanisms of decentralized search for and adaptation to technological and organizational novelties.
Keywords: 330; Lernprozess; Technischer Fortschritt; Globalisierung; Einkommensverteilung; Wirtschaftswachstum